Penerapan Anyaman dan Lukis Kain pada Ready to Wear Style Exotic Dramatic Wayang Krisna - Suci Erlawati; Mien Zyahratil Umami; Romadhona Chusna Tsani (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
Weaving and fabric painting techniques were alternative in making textile motif designs for Ready to Wear. The exclusive value of fabric painting could be a proponent of more beautiful and unique clothing. The problem studied was how to apply weave and fabric painting to clothing and making Ready To Wear exotic dramatic style of Wayang Krisna. The aim of this report was to find out the application of weave and fabric painting in the manufacture of Ready To Wear exotic dramatic style of wayang Krisna. The method used was R&D.The process of making Ready To Wear includes determining the fashion design, preparing tools and materials, applying measurements, making basic patterns, cutting materials, marking the stitches on the fabric, ironing upholstery, and sewing clothes. The materials for this dress were red and black drill fabric, red and black toyobo fabric and batik Sekar Jagat fabric. Using variations of woven and painted fabrics on Ready To Wear with an exotic dramatic style of Wayang Krisna. The use of brushes should be in a smooth way and not pressed firmly, in order to produce natural color strokes and form fine bristles. The process of pressing fabric painting should be at a temperature of 150 degrees and the material part was given a fabric base so that the fabric painting part was not wreck.